2014
DOI: 10.1016/j.jvs.2014.03.288
|View full text |Cite
|
Sign up to set email alerts
|

Carotid angioplasty and stenting is safe and effective for treatment of recurrent stenosis after eversion endarterectomy

Abstract: Carotid artery stenting is safe and reliable procedure for CR after eversion endarterectomy treatment, with low rate of postprocedural complications. Type of stent and cerebral embolic protection device may influence the rate of postprocedural neurologic ischemic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…15 Also, Radak et al reported that no TIAs or strokes were verified during the follow-up, and non-neurologic mortality was 3.13%. 18 No ischemic events were observed during the follow-up period in any of the six patients reported by Heck. 28 Other studies did not provide long-term risk of treatments.…”
Section: Complicationsmentioning
confidence: 75%
See 2 more Smart Citations
“…15 Also, Radak et al reported that no TIAs or strokes were verified during the follow-up, and non-neurologic mortality was 3.13%. 18 No ischemic events were observed during the follow-up period in any of the six patients reported by Heck. 28 Other studies did not provide long-term risk of treatments.…”
Section: Complicationsmentioning
confidence: 75%
“…However, Chung et al reported a >50% restenosis, 32 Radak et al reported that the stenosis was >50% for symptomatic patients and >80% for asymptomatic patients. 18 In the balloon angioplasty and CEA groups, the diameter stenosis was larger than 70%.…”
Section: Factors Affecting the Prognosismentioning
confidence: 94%
See 1 more Smart Citation
“…Radak et al 14 reported that, in 319 patients who underwent carotid angioplasty, coronary artery disease and smoking history were associated with an adverse outcome after carotid angioplasty. Alcohol consumption may be a potentially modifiable risk factor for stroke 15…”
Section: Discussionmentioning
confidence: 99%
“…29 Carotid artery dissections may also be visualized after carotid intervention, occurring in less than 1% of patients undergoing CEA. 30 Ultrasonographic imaging shows an echogenic intimal flap or double lumen within the vessel, which is often associated with an abnormal pattern of flow (Fig. 21).…”
Section: Postoperative Carotid Imagingmentioning
confidence: 99%